ANALYSIS OF CALCULATIONS FOR RECORDING AND REPORTING PPH ARTICLE 23 AT PT. BANK OF SUMUT HEAD OFFICE - Sirait, Ahmad Fauzan; Sanjaya, Surya (Proceeding International Seminar of Islamic Studies, 2024)
In accordance with the problems posed in the research, the aim of this researcher is to find out the analysis of calculating, recording and reporting PPh Article 23 at PT. North Sumatra Bank Head Office. The data analysis technique in this research was carried out using a documentation study, namely by studying, collecting several documents and direct interviews with employees of the finance and planning division in the tax sector which are related to the research problem to be discussed as well as analyzing secondary data regarding Income Tax Article 23. Based on the research results, The process of calculating PPh Article 23 carried out by PT. Bank Sumut Head Office is not yet 100% in accordance with Law Number 36 of the Year. This is because during the process of correcting the Periodic Income Tax Return Article 23 for February 2021, it was discovered that there were several pieces of evidence that had not been uploaded. An error occurred in recording PPh Article 23, namely incorrectly entering the tax deposit code made by PT. Bank Sumut in making deposits.